2018
DOI: 10.1016/j.rmcr.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma presenting as recurrent hydro-pneumothorax: An atypical case presentation and literature review

Abstract: Malignant Pleural Mesothelioma (MPM) is a rare pleural malignancy, with a vague presentation complicated by a decades-long latency period between environmental exposure and clinical manifestations. Spontaneous hydro-pneumothorax is a rare presentation of MPM, most often requiring invasive tissue biopsy to confirm the etiologic diagnosis. We present the case of 79-year-old male smoker with no documented history of asbestos exposure, who was found to have MPM after presenting with dyspnea and subsequently found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The prognosis in these cases is uniformly poor at 6 to 17 months. 3,4,18 For mesothelioma in situ, there are no clear recommendations yet on the optimal treatment approach. 19,20 Close follow up and monitoring is recommended at a minimum due to the potential of progression of mesothelioma in situ to invasive mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognosis in these cases is uniformly poor at 6 to 17 months. 3,4,18 For mesothelioma in situ, there are no clear recommendations yet on the optimal treatment approach. 19,20 Close follow up and monitoring is recommended at a minimum due to the potential of progression of mesothelioma in situ to invasive mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Chest imaging generally reveals pleural-based plaques invading the chest wall and/or pleural effusion. [1][2][3][4][5] Rarely malignant mesothelioma has presented with spontaneous pneumothorax. However, these cases were locally advanced with significant pleural and chest wall invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitsui et al [ 33 ], reviewing Japanese literature, reported a total of 16 MPM patients with spontaneous pneumothorax: 81% were male, and concurrent pleural effusion was present in 56% of cases. Recently, Sattar and colleagues [ 34 ] focused exclusively on patients with MPM presenting as hydropneumothorax. In their literature review, nine cases were collected: a right-sided predominance was observed, exclusively related to the male population, mainly with significant tobacco history.…”
Section: Case Presentation and Discussionmentioning
confidence: 99%
“…While pleural effusions associated with pleural-based masses are common, literature review suggests that hydropneumothorax is exceedingly rare and is predominantly right-sided, making this case of a left-sided hydropneumothorax particularly unique. A pathophysiological explanation for this right-sided predominance is unknown 26–31. One suggested aetiology in these patients is pleural tumour necrosis or necrosis of regional lung metastases leading to failure of the visceral pleura 27 32 33.…”
Section: Discussionmentioning
confidence: 99%